Formation OF NANOCOMPOSITE MATERIALS BASED ON POROUS SILICON AND ZINC OXIDE BY ELECTROCHEMICAL TECHNIQUE - A. I. Sherstnyov; E. B. Chubenko; S. V. Redko; V. A. Petrovich; V. A. Pilipenko; V. P. Bondarenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of electrochemical deposition of zinc oxide into ordered porous silicon matrix, formed in a pulsed galvanostatic mode, are presented. Correlations between zinc oxide nanocrystals growth and electrochemical deposition parameters, such as cathode current density, electrolyte composition, process duration were determined. Structural and optical properties of porous silicon/zinc oxide nanocomposites were studied.